AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH AT TENTH GRADE OF SMA SWASTA NURUL IMAN TANJUNG MORAWA - Sholihatul Hamidah Daulay; Siti Ismahani; Willy Suari (UIN Sumatera Utara, 2022)
This research is aimed to find out students’ difficulties in speaking English at tenth grade of SMA Swasta Nurul Iman Tanjung Morawa. This research is tried to find the students’ difficulties in speaking English, the cause of students’ difficulties in speaking English, and the solution of students’ difficulties in speaking English. This research was used qualitative method. The respondent of this research is the students class X-IIS 3 that consist 10 students. The respondent was chose by used purposive sampling technique. The data collected from the observation, interview, and questionnaire. The questionnaire used Linkert Scale that consists of 15 questions. The result of this research showed that the most from respondent have difficulties in speaking English. The students have difficulties in pronunciation, lack of grammar, difficult to memorize vocabulary, afraid to speak, shy to speak in front of the class, not confidence, and have no motivation in learning speaking English. Furthermore, the cause of students’ difficulties of the research that happened are the lack of grammar, lack of motivation, shyness, anxiety, and afraid making mistakes. The researcher also found the solution of students’ difficulties in speaking English, namely the students needed to condusive class, the new strategies from the teachen when teaching speaking English, and also the teacher must give more knowledge for the students.